An ensemble-based hotel recommender system using sentiment analysis and aspect categorization of hotel reviews - Ray, Biswarup; Garain, Avishek; Sarkar, Ram (Applied soft computing, 2021)
Finding a suitable hotel based on user’s need and affordability is a complex decision-making process. Nowadays, the availability of an ample amount of online reviews made by the customers helps us in this regard. This very fact gives us a promising research direction in the field of tourism called hotel recommendation system which also helps in improving the information processing of consumers. Real-world reviews may showcase different sentiments of the customers towards a hotel and each review can be categorized based on different aspects such as cleanliness, value, service, etc. Keeping these facts in mind, in the present work, we have proposed a hotel recommendation system using Sentiment Analysis of the hotel reviews, and aspect-based review categorization which works on the queries given by a user. Furthermore, we have provided a new rich and diverse dataset of online hotel reviews crawled from Tripadvisor.com. We have followed a systematic approach which first uses an ensemble of a binary classification called Bidirectional Encoder Representations from Transformers (BERT) model with three phases for positive–negative, neutral–negative, neutral–positive sentiments merged using a weight assigning protocol. We have then fed these pre-trained word embeddings generated by the BERT models along with other different textual features such as word vectors generated by Word2vec, TF–IDF of frequent words, subjectivity score, etc. to a Random Forest classifier. After that, we have also grouped the reviews into different categories using an approach that involves fuzzy logic and cosine similarity. Finally, we have created a recommender system by the aforementioned frameworks. Our model has achieved a Macro F1-score of 84% and test accuracy of 92.36% in the classification of sentiment polarities. Also, the results of the categorized reviews have formed compact clusters. The results are quite promising and much better compared to state-of-the-art models. The relevant codes and notebooks can be found here. •Designed a Hotel Recommendation System based on online review in English language.•Ensemble of BERT and Random Forest models for classifying sentiments on reviews.•Used textual features like Word2Vec embeddings and TF–IDF scores.•Categorized the reviews based on aspects using Fuzzy logic and Cosine similarity.•Prepared a sentiment tagged dataset from Tripadvisor consisting of hotel reviews.